Intraparotid facial nerve schwannoma: a 17-year, single-institution experience of diagnosis and management. (4th May 2019) - Li, Shijun; Lu, Xuguang; Xie, Shang; Li, Zimeng; Shan, Xiaofeng; Cai, Zhigang
Abstract: Background: Intraparotid facial nerve schwannoma (IFNS) is rare and its definite preoperative diagnosis is challenging. Objective: To improve available knowledge regarding the diagnosis of IFNS and to suggest an appropriate treatment plan. Material and methods: We retrospectively analyzed medical records of IFNS patients at our hospital. Inclusion criteria were surgery (from January 2000, to December 2016) for a parotid mass, pathologically diagnosed as a schwannoma. Results: The study included 42 eligible patients who had undergone tumor resection from 5977 parotid tumor patients. Mostly presented hard-textured (18/39) or medium-textured (15/39), with limited mobility (21/39) mass (three tumors were not palpable). Their facial nerve function outcomes were House–Brackmann Grade I ( n  = 14), Grade II ( n  = 7), Grade III ( n  = 11), Grade IV ( n  = 5), Grade V ( n  = 3), and Grade VI ( n  = 2). Significant differences were noted in results based on different surgical methods used ( p  = .000) and tumor involvement ( p  = .002). Conclusions and significance: A hard-textured tumor with limited mobility mass in the parotid gland should prompt the diagnosis of a schwannoma. Tumors involving main trunk usually lead to unsatisfactory facial nerve outcomes. Facial nerve preservation should always be essential, and stripping surgery or intracapsular enucleation could be the preferred surgical methods of choice.